Photodynamic Therapy with Hypericin Improved by Targeting HSP90 Associated Proteins - Peter Ferenc; Zuzana Solárová; Mária Chytilová; Peter Fedoročko; Ján Mojžiš; Peter Solár (MDPI AG, 2011)
In this study we have focused on the response of SKBR-3 cells to both single 17-DMAG treatment as well as its combination with photodynamic therapy with hypericin. Low concentrations of 17-DMAG without any effect on survival of SKBR-3 cells significantly reduced metabolic activity, viability and cell number when combined with photodynamic therapy with hypericin. Moreover, IC10 concentation of 17-DMAG resulted in significant increase of SKBR-3 cells in G1 phase of the cell cycle, followed by an increase of cells in G2 phase when combined with photodynamic therapy. Furthermore, 17-DMAG already decreased HER2, Akt, P-Erk1/2 and survivin protein levels in SKBR-3 cells a short time after its application. In this regard, 17-DMAG protected also SKBR-3 cells against both P-Erk1/2 as well as survivin upregulations induced by photodynamic therapy with hypericin. Interestingly, IC10 concentration of 17-DMAG led to total depletion of Akt, P-Erk1/2 proteins and to decrease of survivin level at 48 h. On the other hand, 17-DMAG did not change HER2 relative expression in SKBR-3 cells, but caused a significant decrease of HER2 mRNA in MCF-7 cells characterized by low HER2 expression. These results show that targeting HSP90 client proteins increases the efficiency of antineoplastic effect of photodynamic therapy in vitro.